MALAM BAKURUANG (BERKURUNG) DALAM PERKAWINAN ALEK GADANG DI KENAGARIAN SALAYO KECAMATAN KUBUNG KABUPATEN SOLOK - Iriani, Zora (Humanus, 2012)
This research is conducted in the Salayo Nagari (local state), Kubung District, Solok Regency. There, the traditional wedding Perkawinan Alek Gadang includes the interesting ceremony of Malam Bakuruang, which is celebrated by slaughtering cow and water buffalo. There are several activities in the wedding; pulang dahulu (the groom comes home after the akad nikah (marriage contract), before the wedding ceremony), maanta nasi patang (the bride’s family presents foods for the groom’s family in the afternoon after the groom’s home), manurunkan marapulai (dress the groom), maanta marapulai (escort the groom to the bride’s house), malam bakuruang (the slaughtering ceremony), and arak-arakan (parade). Key words: Minangkabau traditional wedding, Alek Gadang, Malam Bakuruang